Preserving Balinese Folklore: The Development of 'The Origins of Buleleng and Singaraja' via Augmented Reality - I Ketut Yudi Premana Giri; I Gede Mahendra Darmawiguna; Ida Bagus Nyoman Pascima (Universitas Multimedia Nusantara, 2026)
This study presents the development and validation of an Augmented Reality (AR) application centered on the Balinese folklore